Optical and Photoelectric Properties of Nanolamellar Structures Obtained by Thermal Annealing of InSe Plates in Zn Vapours (Phys. Status Solidi A 4∕2018). Issue 4 (21st February 2018) - Untila, Dumitru; Evtodiev, Igor; Caraman, Iuliana; Spalatu, Nicolae; Dmitroglo, Liliana; Caraman, Mihail
Abstract : Lately, an increased attention is paid to AIIIBVI semiconductors (A = Ga, In; B = S, Se, Te), due to their layered structure and weak chemical bonds between elementary packings (B‐AA‐B), which allow an easily obtaining of lamella consisting of one/several packings, by cleavage or exfoliation of single crystals. Due to above‐mentioned aspects, these materials are promising for applications in 2D electronics and optoelectronics. Here, the results of structural, optical and photoelectric properties analysis of InSe crystals grown by Bridgman‐Stockbarger method, and InSe lamella thermally annealed in Zn vapours, are presented. The analysis revealed the ZnSe compound formation onto surface of InSe plates. The ZnSe‐InSe composite layer and the composite/InSe heterojunction are photosensitive and photoluminescent in the VIS‐NIR spectral region. This is reported by Dumitru Untila and co‐workers in article number1700434 .